2020
DOI: 10.1021/acs.langmuir.0c02349
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously Large Assembly Formation of Polystyrene Nanoparticles by Optical Trapping at the Solution Surface

Abstract: We demonstrated the optical trapping-induced formation of a single large disc-like assembly (∼50 μm in diameter) of polystyrene (PS) nanoparticles (NPs) (100 nm in diameter) at a solution surface. Different from the conventional trapping behavior in solution, the assembly grows from the focus to the outside along the surface and contains needle structures expanding radially in all directions. Upon switching off the trapping laser, the assembly disperses and needle structures disappear, while the highly concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…A single large assembly containing fiber-like aggregates disappeared upon turning off the trapping laser, and it recovered after turning it on again. It is notable, furthermore, that this assembling of the 100 nm PS NPs occurs around a single 10 μm PS MP, which is exclusively irradiated at the surface . In both cases with and without the big 10 μm PS MP, we could not observe clearly scattering and propagation of the trapping laser which enables the formation of such the wide assembly.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…A single large assembly containing fiber-like aggregates disappeared upon turning off the trapping laser, and it recovered after turning it on again. It is notable, furthermore, that this assembling of the 100 nm PS NPs occurs around a single 10 μm PS MP, which is exclusively irradiated at the surface . In both cases with and without the big 10 μm PS MP, we could not observe clearly scattering and propagation of the trapping laser which enables the formation of such the wide assembly.…”
Section: Resultsmentioning
confidence: 74%
“…It is notable, furthermore, that this assembling of the 100 nm PS NPs occurs around a single 10 μm PS MP, which is exclusively irradiated at the surface. 41 In both cases with and without the big 10 μm PS MP, we could not observe clearly scattering and propagation of the trapping laser which enables the formation of such the wide assembly. As an alternative possible mechanism to realize such a long-range interaction between the focus and whole area of the assembly, we suggested an electrostatic interaction started at the focused area.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Wu et al also demonstrated the large-scale optical assembly of PS particles into needle-like structures in the radial direction with the assistance of negative thermophoresis and thermal convection. 306 Through the coordination of natural convective flow, negative thermophoresis, and optical force, Ho and co-workers demonstrated long-range and 3D optical trapping of PS beads and Escherichia coli (E. coli) bacteria (Figure 19e). 307 The convective flow was exploited to transport dispersed particles toward the Au-coated fiber tip.…”
Section: Optothermal Assembly Based On Natural Convectionmentioning
confidence: 99%
“…In 2015, the first optically evolved assembly was reported by trapping polystyrene (PS) NPs at the air/solution interface . Since then, several kinds of optically evolved assemblies were reported using PS particles at both air/solution and glass/solution interfaces. The formation of these assemblies is driven by the expansion of the optical potential through light propagation from the irradiated constituents. However, the basis of the “optically evolved phenomena” is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%